Motivational factors and negative affectivity as predictors of alcohol craving. (30th September 2016) - Pombo, Samuel; Luísa Figueira, M.; Walter, Henriette; Lesch, Otto
Abstract: Craving is thought to play an important role in alcohol use disorders. The recent inclusion of "craving" as a formal diagnostic symptom calls for further investigation of this subjective phenomenon with multiple dimensions. Considering that alcohol-dependent patients compensate negative physical/emotional states with alcohol, the aim of this study is to investigate alcohol craving and its correlation with drinking measures and affective personality dimensions. A sample of 135 alcohol-dependent patients (104 males and 31 females) was collected from a clinical setting. Subjects self-rated their cravings (Penn Alcohol Craving Scale) and the stage of change. Several personality scales were also administered. Craving was related to drinking status, abstinence time, age, and taking steps. After controlling for these conditions, psychological characteristics related to low self-concept, neuroticism, cyclothymic affective temperament, depression, and hostility were found to be predictors of craving in sober alcohol-dependent patients. Our results support craving as a component of the phenomenology of alcohol dependence and highlight the presence of unpleasant feelings as predictors of craving in sober alcohol-dependent patients without co-occurring psychiatric conditions. The predisposition to experience negative emotions may induce a stronger craving response and increase the likelihood of a first drink and a subsequent loss of control. Highlights: We tested associations between craving, drinking, and personality-related variables. Data were collected in an ambulatory clinical setting. Craving showed a negative correlation with abstinence and motivation to change. Craving was positively associated with neuroticism and cyclothymic affective temperament. Negative affects are considered to increase craving in sober alcohol-dependent patients.